Plasma IL‐12/IFN‐γ axis predicts cognitive trajectories in cognitively unimpaired older adults. Issue 4 (23rd June 2021) - Yang, Hyun‐Sik; Zhang, Can; Carlyle, Becky C.; Zhen, Sherri Y.; Trombetta, Bianca A.; Schultz, Aaron P.; Pruzin, Jeremy J.; Fitzpatrick, Colleen D.; Yau, Wai‐Ying W.; Kirn, Dylan R.; Rentz, Dorene M.; Arnold, Steven E.; et al.
Abstract: Introduction: Immune dysregulation is implicated in neurodegeneration and altered cytokine levels are seen in people with dementia. However, whether cytokine levels are predictive of cognitive decline in cognitively unimpaired (CU) elderly, especially in the setting of elevated amyloid beta (Aβ), remains unclear. Methods: We measured nine cytokines in the baseline plasma of 298 longitudinally followed CU elderly and assessed whether these measures were associated with cognitive decline, alone or synergistically with Aβ. We next examined associations between cytokine levels and neuroimaging biomarkers of Aβ/tau/neurodegeneration. Results: Higher IL‐12p70 was associated with slower cognitive decline in the setting of higher Aβ (false discovery rate [FDR] = 0.0023), whereas higher IFN‐γ was associated with slower cognitive decline independent of Aβ (FDR = 0.013). Higher IL‐12p70 was associated with less tau and neurodegeneration in participants with higher Aβ. Discussion: Immune dysregulation is implicated in early‐stage cognitive decline, and greater IL‐12/IFN‐γ axis activation may be protective against cognitive decline and early‐stage AD progression.